Ceria-stabilized zirconia-based composites printed by stereolithography: Impact of the processing method on the ductile behaviour and its transformation features. Issue 7 (July 2023) - Fournier, Sylvain; Chevalier, Jérôme; Baeza, Guilhem P.; Chaput, Christophe; Louradour, Eric; Sainsot, Philippe; Cavoret, Jérôme; Reveron, Helen
Abstract: A commercial composite powder was used to develop a new paste for stereolithography processing (SLA) of dense 11Ce-TZP-based composites containing 8 vol.% of alumina and 8 vol.% of strontium aluminate. The same powder was used to prepare reference ceramics by conventional Cold Isostatic Pressing (CIP) and sintering. The use of SLA gave rise to a microstructure containing larger strontium aluminate clustering surrounded by zirconia grains devoid of alumina particles, which appeared embedded in a matrix of zirconia-alumina grains. This slightly more heterogeneous microstructure favoured the formation of a greater number of thinner transformation bands, causing a larger plastic deformation in SLA samples (failure strain of 0.65 % instead of 0.35 % for CIP samples), without compromising characteristic strength ( σ 0 = 560 and 586 MPa respectively). Thus, SLA does not affect the ductile behaviour that characterizes this type of ceramics and appears as a very promising method for the development of custom-made ceramic prostheses.